Structures and stability of simple DNA repeats from bacteria - Brazda, Vaclav; Fojta, Miroslav; Bowater, Richard P (The Biochemical journal, 2020)
DNA is a fundamentally important molecule for all cellular organisms due to its biological role as the store of hereditary, genetic information. On the one hand, genomic DNA is very stable, both in chemical and biological contexts, and this assists its genetic functions. On the other hand, it is also a dynamic molecule, and constant changes in its structure and sequence drive many biological processes, including adaptation and evolution of organisms. DNA genomes contain significant amounts of repetitive sequences, which have divergent functions in the complex processes that involve DNA, including replication, recombination, repair, and transcription. Through their involvement in these processes, repetitive DNA sequences influence the genetic instability and evolution of DNA molecules and they are located non-randomly in all genomes. Mechanisms that influence such genetic instability have been studied in many organisms, including within human genomes where they are linked to various human diseases. Here, we review our understanding of short, simple DNA repeats across a diverse range of bacteria, comparing the prevalence of repetitive DNA sequences in different genomes. We describe the range of DNA structures that have been observed in such repeats, focusing on their propensity to form local, non-B-DNA structures. Finally, we discuss the biological significance of such unusual DNA structures and relate this to studies where the impacts of DNA metabolism on genetic stability are linked to human diseases. Overall, we show that simple DNA repeats in bacteria serve as excellent and tractable experimental models for biochemical studies of their cellular functions and influences.
Keywords: DNA metabolism; repetitive DNA sequences; Nucleic Acid Conformation; genom lidský; microsatellites; mikrosatelitní repetice; nestabilita genomu; DNA structure; Repetitive Sequences, Nucleic Acid; Genome, Bacterial; Bacteria; Genomic Instability; Genome, Human; Microsatellite Repeats; genom bakteriální; konformace nukleové kyseliny; lidé; Humans; DNA; repetitivní sekvence nukleových kyselin; nucleic acids